1988
DOI: 10.1590/s0101-81751988000100002
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência e caracterização de galhas entomógenas na vegetação do campus pampulha da Universidade Federal de Minas Gerais

Abstract: RESUMO.Obteve-se 37

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
11

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 1 publication
4
38
0
11
Order By: Relevance
“…A different result was found in restingas, where Eulophidae and Eurytomidae were the predominant families. FERNANDES et al (1988) found similar results in their research in Minas Gerais, Brazil. These data suggest that Eulophidae and Eurytomidae may be the most important natural enemies of gall midges in the Neotropical region.…”
Section: Resultssupporting
confidence: 82%
“…A different result was found in restingas, where Eulophidae and Eurytomidae were the predominant families. FERNANDES et al (1988) found similar results in their research in Minas Gerais, Brazil. These data suggest that Eulophidae and Eurytomidae may be the most important natural enemies of gall midges in the Neotropical region.…”
Section: Resultssupporting
confidence: 82%
“…This trend is uncommon for insect galls, which are usually reported to occur predominantly on leaves (DregerJauffret & Shorthouse 1992; Fernandes et al 1988;Maia & Fernandes 2004;Moreira et al 2007;Maia et al 2008). Only a few studies report more galls on stems (African savanna; Veldtman & McGeoch 2003) or stems and buds (rupestrian fields; Carneiro et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Considering gall occurrence, isolated galls were more frequent, as reported by other studies. Fernandes et al (1988) hypothesized that galls which occur isolated would be favored because parasitoid pressure would be diminished due to the greater searching time implied by isolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports of galls in plants of most environments throughout the world (Felt, 1994;Mani, 1964;Gagné, 1989Gagné, , 1994Fernandes et al, 1988Fernandes et al, , 1997b. On the other hand, few authors have reported gall in aquatic macrophytes (Gagné, 1989;Fernandes & Lara, 1997a).…”
Section: (With 12 Figures)mentioning
confidence: 99%